Subscapular skinfold thickness, not other anthropometric and dual-energy X-ray absorptiometry-measured adiposity, is positively associated with the presence of age-related macular degeneration: a cross-sectional study from National Health and Nutrition Examination Survey 2005–2006 - Jayne Woodside; David Wright; Margaret Rayman; Miguel Gedtal; Ruth Esther Hogg (BMJ Open Ophthalmology)
Objective Current literature reveals an association between anthropometric measures of adiposity (AnthM) and age-related macular degeneration (AMD), but few have explored the disease association with imaging methods. This study aimed to explore the relationship between AMD status and dual-energy X-ray absorptiometry measures (DEXAMs) among a representative sample of the US population, and compare the association with AnthM.Method Using a representative sample in the National Health and Nutrition Examination Study 2005–2006 (n=1632), DEXAMs across the whole body and waist (ie, android), and relative fat distributions (eg, percentage fat, android-to-total body ratio) were analysed between no AMD (baseline) and any AMD. Bivariate analyses across AMD status were similarly performed for AnthM (ie, body mass index, waist circumference and skinfold thicknesses) and potential confounders (ie, demographics and health-related variables). Significant adiposity measures were analysed using logistic regression, adjusting for confounders.Results The participants in the sample were aged 40–69 years, were majority female (52%) and mainly Caucasian (76.5%). Bivariate analysis revealed having any AMD had positive significant associations with android-to-total fat ratio and subscapular skinfold thickness (SSFT). Other AnthM and DEXAMs were not significant. After adjusting age, gender and prescription of cholesterol-lowering medicine, only SSFT remained significantly associated.Conclusion SSFT represents an independent risk factor for AMD presence compared with other AnthM and DEXAMs. SSFT is an established method of measuring fat under the skin (ie, subcutaneous fat). Hence, subcutaneous fat may be more relevant in explaining the adiposity–AMD link due to physiological properties specific to the tissue. Limitations include the restricted age range and low numbers of participants with late AMD.